(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Corporate governance plays a crucial role in ensuring transparency, accountability, and ethical conduct in business organizations. However, repeated corporate scandals across the globe highlight the persistent weaknesses in governance frameworks and financial reporting systems. One of the most significant cases in India is the Satyam scandal of 2009, which exposed large-scale accounting fraud and systemic governance failures. This article critically examines the corporate governance breakdown and financial reporting irregularities in Satyam Computer Services Ltd., analyses the role of management, board of directors, auditors, and regulatory authorities, and draws key lessons for strengthening governance mechanisms in India. The study adopts a doctrinal and analytical approach, relying on secondary data sources. The findings emphasize that the Satyam case was not merely an accounting fraud but a comprehensive failure of governance structures, internal controls, and ethical standards. The article concludes by suggesting reforms to enhance corporate governance and financial transparency in India.